Effect of hydroalcoholic extract of Tanacetum parthenium on gene expression and paraoxonase 1 enzyme activity: An experimental and molecular dynamic study - Javad Saffari-Chaleshtori; Fatemeh Maghsoudi; Hojatollah Rohi-Brojeni; Keyhan Ghatreh-Samani (Journal of Shahrekord University of Medical Sciences)
Background and aims: Cardiovascular diseases are among the most common causes of death worldwide. The paraoxonase 1 (PON1) enzyme is a main factor in preventing these diseases. This study investigated the effect of hydroalcoholic extract of Tanacetum parthenium plant on the activity and gene expression of PON1. Methods: Forty male rats were divided into 4 groups: a control group, a hyperlipidemic group, and two hyperlipidemic groups that were treated with 400 and 800 mg/kg of hydroalcoholic extract. Arylesterase activity of PON1 and serum triglyceride and cholesterol levels were measured. Moreover, the gene expression of PON1 in the liver tissue samples was measured using real-time PCR. Finally, molecular dynamics studies of apigenin as a main compound in the plant were performed to investigate the activity of PON1 in the simulated environment. Results: Hydroalcoholic extract of T. parthenium decreased serum triglyceride (from 105.8±10.1 to 60.5±21.5 and 50.9±11.2 mg/dL) and total cholesterol (from 97.5±16.8 to 59.6±8.5 and 52.0±9.6 mg/dL) levels, while it increased the activity of arylesterase paraoxonase1 significantly (P<0.001). It also showed a significant (P<0.001) effect on PON1 gene expression. However, the dose of 800 mg/kg was more effective. The results of simulation and molecular dynamics showed that apigenin binds to PON1 with a high affinity and induces changes in the molecular dynamics parameters. Conclusion: The 800 mg/kg of hydroalcoholic extract of T. parthenium can increase the activity of PON1 and its gene expression. It seems that apigenin as one of the most important antioxidant compounds of this plant can increase the activity of this enzyme by direct binding to PON1.